IN VITRO PROPAGATION OF MORINGA OLEIFERA - & Ameen, Ibrahim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This research was conducted at the plant tissue culture lab. - College of Agriculture – University of Baghdad from February 2015 to May 2016. The Study was aimed to investigate the in vitro propagation of Moringa oleifera, by inoculation a single nodal segment in MS medium supplemented with different concentrations of plant growth regulators. The best responded of single node reached to 90% was achieved with MS medium supplemented with 1 mg. L-1 BA and 0.2 mg. L-1 IAA. At Multiplication stage results showed that MS medium supplemented with 2 mg. L-1 of BA with 0.1 mg. L-1 IAA increased numbers of shoot comparing with the Kin; (6.40 shoot /exp.) While the treatment of MS medium supplemented with 0.2 mg. L-1 IAA without BA gave the best shoots length which reached 4.15 cm. In rooting stage, shoots have been cultured in MS medium supplemented with different concentrations of Auxins. Results showed that MS medium at half strength supplemented with 1 mg. L-1 of IBA and 1.5 mg. L-1 IAA significantly increased the number of roots per shoot, roots length up to (7.2 roots/shoot and 6.14 cm) respectively. The survival percentage of plantlets was 70% when they planted in a composed consisted of 3:1 (v:v) peatmoss: soil mixture. We found that BA increased numbers of shoot comparing with the Kin and MS medium at half strength was the best in rooting plantlet comparing with MS medium at full strength.